Sintesis SiC (Silikon Karbida) Berbahan Dasar Pasir Putih Dan Arang Tempurung Kelapa - Slarmanat, Ruth; Rampe, Meytij; Lombok, John (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
White sand and coconut shell charcoal are materials that are often found in everyday life. White sand and coconut shell charcoal as basic materials in SiC synthesis. By using the alkali fusion method, SiC can be synthesized at lower temperatures. This research aims to identify the characteristics of SiC synthesis from white sand and coconut shell charcoal as the basic material through XRF and FTIR testing. The results of identification through XRF testing showed that the CaO component was 71.30%. The results of FTIR analysis show that the functional group that appears is Si-C at wave numbers 786.89 – 941.19 cm-1